2003
DOI: 10.1515/epoly.2003.3.1.752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymerization sequence on the electrochemical properties of polypyrrole / poly(3-methylthiophene) bilayers

Abstract: The electrochemical and photoelectrochemical characteristics of conducting polymer bilayers composed by polypyrrole, PPy, and poly(3-methylthiophene), PMeT, are described. The bilayers were produced by galvanostatic deposition of the polymers using different charge densities. Scanning electron micrographs indicate that the sequence of polymerization affects the surface morphology of the bilayers and, while PMeT polymerizes into the pores of the PPy film, a PPy film is formed over the PMeT film. Cyclic voltamme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Therefore, the morphological structure of the PPy-p͑TPTC3-PO 3 H 2 ͒ bilayer is dominated by the morphology of the deposited PPy films. Similar observations were made by other authors, reporting that the bilayer was composed of PPy as inner layer and poly͑3-methylthiophene͒, PMeT, 13 or poly͑3-octylthiophene͒ 37 as outer layers.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the morphological structure of the PPy-p͑TPTC3-PO 3 H 2 ͒ bilayer is dominated by the morphology of the deposited PPy films. Similar observations were made by other authors, reporting that the bilayer was composed of PPy as inner layer and poly͑3-methylthiophene͒, PMeT, 13 or poly͑3-octylthiophene͒ 37 as outer layers.…”
Section: Resultssupporting
confidence: 91%
“…It has been reported that bilayers composed of PPy as the inner layer and pMeT as the outer layer, present a similar picture. 43,13 When a reduction pulse is applied from OCP to −0.6 V ͑curve e in Fig. 7͒ in 0.1 M tris/HCl buffer, the intensity of the absorbance at 800-nm band decreases.…”
Section: Journal Of the Electrochemical Society 152 ͑11͒ E345-e350 ͑2...mentioning
confidence: 99%
See 1 more Smart Citation